Suppression of SlMBP15 Inhibits Plant Vegetative Growth and Delays Fruit Ripening in Tomato - Yin, Wencheng; Yu, Xiaohui; Chen, Guoping; Tang, Boyan; Wang, Yunshu; Liao, Changguang; Zhang, Yanjie; Hu, Zongli (Frontiers in Plant Science, 2018)
MADS-box genes have been demonstrated to participate in a number of processes in tomato development, especially fruit ripening. In this study, we reported a novel MADS-box gene, SlMBP15, which is implicated in fruit ripening. Based on statistical analysis, the ripening time of SlMBP15-silenced tomato was delayed by 2–4 days compared with that of the wild-type (WT). The accumulation of carotenoids and biosynthesis of ethylene in fruits were decreased in SlMBP15-silenced tomato. Genes related to carotenoid and ethylene biosynthesis were greatly repressed. SlMBP15 can interact with RIN, a MADS-box regulator affecting the carotenoid accumulation and ethylene biosynthesis in tomato. In addition, SlMBP15-silenced tomato produced dark green leaves, and its plant height was reduced. The gibberellin (GA) content of transgenic plants was lower than that of the WT and GA biosynthesis genes were repressed. These results demonstrated that SlMBP15 not only positively regulated tomato fruit ripening but also affected the morphogenesis of the vegetative organs.